1996
DOI: 10.2494/photopolymer.9.355
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity of Aliphatic Polyimide.

Abstract: Photoconductivity of an aliphatic polyimide, PI(PMDA/DCHM), was investigated, comparing with that of an aromatic polyimide, PI(PMDA/ODA). An enhanced photocurrent was observed for the aliphatic polyimide. The quantum efficiency of the aliphatic polyimide and the aromatic polyimide was 2.1x10-5 at 370 nm, as 5.6x10-6 at 420 nm respectively, where the film thickness is 1.0 µ. Initial photoresponse behavior was observed to investigate the photoconductoon mechanism of the aliphatic polyimide, which shows a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The region which shows the enhanced photocurrent by the addition of TMPD is attributed to the intermolecular charge-transfer complex formed between the pyromellitic imide unit and TMPD. In our previous paper, 20 fluorescence spectra of the polyimide film with the alicyclic diamine, PI(PMDA/DCHM), showed a strong monomer emission for 300-320 nm excitation and red-shifting emission for longer wavelength (380-450 nm) excitation, suggesting that species responsible to this red-shifting emission is related to the photoconductivity of the polyimide film with the alicyclic diamine without an electron donor. However, for TMPD-doped PI(PMDA/DCHM) and PI(PMDA/O-DA) films, we observed the intermolecular chargetransfer complex formed between pyromellitic imide unit and TMPD by measuring absorption spectra ( Figure 4) and also fluorescence spectra with very weak structureless broad band at 590 nm.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The region which shows the enhanced photocurrent by the addition of TMPD is attributed to the intermolecular charge-transfer complex formed between the pyromellitic imide unit and TMPD. In our previous paper, 20 fluorescence spectra of the polyimide film with the alicyclic diamine, PI(PMDA/DCHM), showed a strong monomer emission for 300-320 nm excitation and red-shifting emission for longer wavelength (380-450 nm) excitation, suggesting that species responsible to this red-shifting emission is related to the photoconductivity of the polyimide film with the alicyclic diamine without an electron donor. However, for TMPD-doped PI(PMDA/DCHM) and PI(PMDA/O-DA) films, we observed the intermolecular chargetransfer complex formed between pyromellitic imide unit and TMPD by measuring absorption spectra ( Figure 4) and also fluorescence spectra with very weak structureless broad band at 590 nm.…”
mentioning
confidence: 89%
“…One of the reasons for their high performance is due to the elimination of charge transfer, because the charge transfer state of aromatic polyimides is formed between aromatic diamines as electron donors and aromatic dianhydrides as electron acceptors both intra-and intermolecularly. 17 -19 In our previous paper, 20 the photoconductivity of the polyimide film prepared from pyromellitic dianhydride (PMDA) and diaminodicyclohexylmethane (DCHM), PI(PMDA/DCHM) has been investigated, compared with that of an aromatic polyimide prepared from PMDA and oxydianiline (ODA), PI(PMDA/ODA). We have found that the polyimide film with the alicyclic diamine as well as the aromatic polyimide film showed the photoconductive properties even without the addition of any electron donors.…”
mentioning
confidence: 99%
“…[4][5][6]9 The electrical conduction behaviors of PMDA/ODA films have been investigated by several research groups. [10][11][12][13][14][15][16][17][18][19] Sawa et al 13 studied the electric conduction current of PMDA/ODA films at temperatures of 120-180 1C and applied electric fields of 4 À500 kV cm À1 . They concluded that the conduction in the PI films is caused by ionic hopping.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that both enhancement in the charge mobility and an increase in the number of electronic carriers in the bulk are necessary to improve the conductivity of PIs. Lee et al [17][18][19] investigated the photoconductivity of semi-aliphatic 4,4 0 -diaminodicyclohexylmethane (PMDA/DCHM) PI films. They reported that a charge-transfer complex is formed in the excited state when an optical absorption band assignable to weak intermolecular interactions is excited, and the charge-transfer complex subsequently produces charge carriers of radical cations and radical anions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the polyimides prepared from alicyclic diamines are attracting much interest because they have good optical spectroscopic and dielectric properties as well as good thermal stability. One of the reasons for their high performance is due to the elimination of charge transfer, because the charge-transfer state of aromatic polyimides is formed between the aromatic diamines as electron donors and the aromatic dianhydrides as electron acceptors both intra- and intermolecularly. , In our previous paper, the photoconductivity of the polyimide film, PI(PMDA/DCHM), prepared from pyromellitic dianhydride (PMDA) and diaminodicyclohexylmethane (DCHM) was investigated, compared with that of an aromatic polyimide, PI(PMDA/ODA), prepared from PMDA and oxydianiline (ODA). We reported that the polyimide film prepared from the alicyclic diamine showed equal photoconductive properties compared with the aromatic polyimide film, even without the addition of any donors.…”
Section: Introductionmentioning
confidence: 99%